HEGEMONI TOKOH NYAI SUKU DALAM NASKAH DRAMA GENERASI TERAKHIR KARYA GEPENG NUGROHO - Fibiani, Mufadila; Qur'ani, Hidayah Budi (Jurnal Pena Indonesia, 2020)
This study aims to prove that leaders are not always able to interfere with the personal rights of their members through the hegemony of Nyai Suku in the last generation drama by Gepeng Nugroho. To answer these problems, the Gramshi Hegemony theory is used through a sociological approach. This type of research is qualitative with descriptive form. The data source of this research is the Final Generation drama by Gepeng Nugroho. Data collection techniques are carried out by central study and note it. Data analysis was done by hermeneutic method. The results of this research show that the form of hegemony of Nyai Suku character is in the form of planting new beliefs covertly through the speeches he delivered, habituation through his teachings to communal to answer compactly with sentences that show as if they were strong people, and coercion by giving lashing to its communal members violate the rules.Â